The obsession - Roberts, Nora; McManus, Shannon (Grand Haven, Michigan : Brilliance Audio, 2016)
Years after discovering her father's predatory double life, successful photographer Naomi Bowes struggles to hide her painful past from her fellow residents in a community thousands of miles away, a situation that introduces her to a new relationship and forces her to confront her demons.
Read by Shannon McManus.
Keywords: Man-woman relationships -- Fiction; Fathers and daughters -- Fiction; Audiobooks; Romance fiction